ANALISIS PENGENDALIAN PERSEDIAAN LOW DENSITY POLYETHYLENE (LDPE) DENGAN METODE ECONOMIC ORDER QUANTITY (EOQ) PRODUK CAIRAN INFUS DI PT. WIDATRA BHAKTI: Dwi Puji Lestari - dwi puji lestari (JOURNAL AKSES STIA MALANG, 2019)
Abstract Widatra Bhakti is a pharmaceutical company engaged in producing basic infusion fluids whose 99% of the products are intended for the domestic market and 1% for overseas markets. In conducting its production activities are closely related to the supply of raw materials which are important components that must be available for the smoothness of the production process. The raw material used is LDPE, which is used for the process of making the infusion bottles. This study aims to determine the control of LDPE raw material inventory at PT. Widatra Bhakti and to determine the amount of economical ordering of LDPE raw materials as well as to determine the minimum total inventory cost. This research uses descriptive method that is quantitative because this research relates to the object of research that is on the company with a certain period of time by collecting data and information relating to the company and suited to the purpose of the research. Descriptive analysis techniques used to analyze data on LDPE raw material inventory control problem in an effort to reduce the inventory cost using Economic Order Quantity (EOQ) method. The result shows that the company can save costs with fewer purchase frequencies if the EOQ method is used where inventory costs are more cost-effective than using current company-run methods is used. Keywords: Inventory Control, EOQ, Inventory Cost